1992
DOI: 10.1148/radiology.184.3.1324509
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver disease: comparison of dynamic contrast-enhanced CT and T2-weighted fat-suppressed, FLASH, and dynamic gadolinium-enhanced MR imaging at 1.5 T.

Abstract: Dynamic contrast medium-enhanced computed tomography (CT), T2-weighted fat-suppressed spin-echo (T2FS) magnetic resonance (MR) imaging, and breath-hold T1-weighted fast low-angle shot (FLASH) MR imaging before and after dynamic gadopentetate dimeglumine injection were compared in 73 patients with clinically suspected liver disease. Observer confidence for presence of focal lesions was determined by using receiver operating characteristic analysis. For all MR images, hepatic lesion-liver signal-to-noise ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(66 citation statements)
references
References 0 publications
4
58
0
4
Order By: Relevance
“…While dynamic contrast examination has become a component of routine abdominal scans, the contrast material used increases costs and carries the risk of side effects. Additionally, in some cases, distinguishing vascular metastasis from hemangioma is not possible even with dynamic examination 16 . DWI is a technique which can be used within the duration of a held breath with no necessity for contrast material, and it helps to distinguish the "benign-malignant" nature of many focal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…While dynamic contrast examination has become a component of routine abdominal scans, the contrast material used increases costs and carries the risk of side effects. Additionally, in some cases, distinguishing vascular metastasis from hemangioma is not possible even with dynamic examination 16 . DWI is a technique which can be used within the duration of a held breath with no necessity for contrast material, and it helps to distinguish the "benign-malignant" nature of many focal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiolabeled RBC scintigraphy is a reliable test for the diagnosis of hepatic cavernous he mangioma, it does not readily localize small lesions and has a significant false-positive rate [2,4]. It also provides limited information on disease conditions other than hemangioma, which often makes subsequent CT or MR im aging necessary [4,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…On MR imaging,cavernous hemangiomais seen as a strong, light bulbâ€"like signal on heavily T2-weightedimages [4,16], and with the ad vantages of dynamic MR imaging (such as a highly concentrated contrast agent injected over a short time and fast image acquisition in the arterial dominant phase),the characteristic dynamic CT findings of hemangioma can be more clearly observed [5,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Spin echo echo-planar imaging (SE-EPI) sequence with single shot breath holding tecnique is performed in DWI. With the development of paralel imaging techniques, imaging time has become shorter, quality of EPI sequence has increased and addition of DWI to routine abdominal imaging has become more effective and popular [4][5][6]. Recent studies have shown the efficacy of quantitative apparent coefficient diffusion (ADC) measurements in differential diagnosis of benign and malignant liver masses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%